PENGARUH TEKNIK PEMBERIAN BALIKAN DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR IPA (Suatu Penelitian Eksperimen di Kelas VIII SMP Negeri 2 Bongomeme) - Suleman Suleman (LPPM Universitas Muhammadiyah Gorontalo, 2018)
The study aimed to find out: (1) differences in science learning outcomes between students who were taught with delayed and direct feedback giving techniques, (2) the interaction effects of feedback techniques and spatial cognitive style on science learning outcomes, (3) differences in science learning outcomes in the group of students who have high spatial cognitive style, those who are taught using delayed and direct feedback giving techniques, (4) differences in science learning outcomes in students who have a low spatial cognitive style, are taught using delayed and reversed direct giving techniques . The method used is tretment by level with 2 x 2 ANAVA design. The results of this study show that the learning outcomes of science in students who are taught by the technique of giving direct natural science learning outcomes are higher than the delayed giving technique. There is an influence of the interaction between the reciprocal giving technique and the cognitive style of the students towards the learning outcomes of science. Students who have a high spatial cognitive style learned by the technique of giving direct feedback to science learning outcomes are higher than the delayed giving technique. For students who have a low spatial cognitive style, learning techniques for giving direct feedback to science learning outcomes are lower than delayed feedback techniques. Penelitian bertujuan untuk mengetahui: (1) perbedaan hasil belajar IPA antara peserta didik yang dibelajarkan dengan teknik pemberian balikan langsung dan balikan tertunda, (2) pengaruh interaksi teknik pemberian balikan dan gaya kognitif spasial terhadap hasil belajar IPA, (3) perbedaan hasil belajar IPA pada kelompok peserta didik yang memiliki gaya kognitif spasial tinggi, yang dibelajarkan dengan menggunakan teknik pemberian balikan langsung dan balikan tertunda, (4) perbedaan hasil belajar IPA pada peserta didik yang memiliki gaya kognitif spasial rendah, dibelajarkan dengan menggunakan teknik pemberian balikan langsung dan balikan tertunda. Metode yang digunakan adalah tretmen by level dengan rancangan desain ANAVA 2 x 2. Hasil dari penelitian ini menunjukan hasil belajar IPA pada peserta didik yang dibelajarkan dengan teknik pemberian balikan langsung hasil belajar IPA lebih tinggi daripada teknik pemberian balikan tertunda. Terdapat pengaruh interaksi antara teknik pemberian balikan dan gaya kognitif peserta didik terhadap hasil belajar IPA. Peserta didik yang memiliki gaya kognitif spasial tinggi yang dibelajarkan dengan teknik pemberian balikan langsung hasil belajar IPA lebih tinggi daripada teknik pemberian balikan tertunda. Untuk peserta didik yang memiliki gaya kognitif spasial rendah, dibelajarkan dengan teknik pemberian balikan langsung hasil belajar IPA lebih rendah daripada teknik pemberian balikan tertunda.